## Trending News

# calculus is hard need help!?

### 2 Answers

- la consoleLv 71 month agoFavorite Answer
f(x) = 2x².(3x - 9)

The function f looks like (u.v), so its derivative looks like: (u'.v) + (v'.u) → where:

u = 2x² → u' = 4x

v = 3x - 9 → v' = 3

f'(x) = (u'.v) + (v'.u)

f'(x) = 4x.(3x - 9) + (3 * 2x²)

f'(x) = 12x² - 36x + 6x²

f'(x) = 18x² - 36x

f(x) = (3x - 6)/[x.(x + 6)]

f(x) = (3x - 6)/(x² + 6x)

The function f looks like (u/v), so its derivative looks like: [(u'.v) - (v'.u)]/v² → where:

u = 3x - 6 → u' = 3

v = x² + 6x → v' = 2x + 6

f'(x) = [(u'.v) - (v'.u)]/v²

f'(x) = [3.(x² + 6x) - (2x + 6).(3x - 6)]/(x² + 6x)²

f'(x) = [3x² + 18x - (6x² - 12x + 18x - 36)]/(x² + 6x)²

f'(x) = [3x² + 18x - (6x² + 6x - 36)]/(x² + 6x)²

f'(x) = [3x² + 18x - 6x² - 6x + 36]/(x² + 6x)²

f'(x) = [- 3x² + 12x + 36]/(x² + 6x)²

f'(x) = 3.(- x² + 4x + 12)/(x² + 6x)²

f(x) = [(x³ - 1)⁵ + 2]³ → recall the derivative of u^(n) → n * u' * n^(n - 1)

f'(x) = 3 * [(x³ - 1)⁵ + 2]' * [(x³ - 1)⁵ + 2]² → the derivative of 2 is zero

f'(x) = 3 * [(x³ - 1)⁵]' * [(x³ - 1)⁵ + 2]²

f'(x) = 3.[5 * (x³ - 1)' * (x³ - 1)⁴] * [(x³ - 1)⁵ + 2]² → the derivative of 1 is zero

f'(x) = 3.[5 * (x³)' * (x³ - 1)⁴] * [(x³ - 1)⁵ + 2]²

f'(x) = 3.[5 * (3x²) * (x³ - 1)⁴] * [(x³ - 1)⁵ + 2]²

f'(x) = 3.[15x² * (x³ - 1)⁴] * [(x³ - 1)⁵ + 2]²

f'(x) = 45x².(x³ - 1)⁴.[(x³ - 1)⁵ + 2]²

- Anonymous1 month ago
As many do, it is an Educational Fraud.

less than 5% of Students will need let a lone use Calculus in their professional lives.

Same with Second Languages.

Stress on students, unnecessary money making classes.